Public policy and the creation of active venture capital markets - Marco Da Rin; Giovanna Nicodano; Alessandro Sembenelli (European Central Bank (ECB), 2005)
We study how public policy can contribute to increase the share of early stage and high-tech venture capital investments, thus helping the development of active venture capital markets. A simple extension of the seminal model by Holmstrom and Tirole (1997) provides a theoretical base for our analysis. We then explore a unique panel of data for 14 European countries between 1988 and 2001. We have several novel findings. First, the opening of stock markets targeted at entrepreneurial companies positively affects the shares of early stage and high-tech venture capital investments; reductions in capital gains tax rates have a similar, albeit weaker, effect. Second, a reduction in labor regulation creases the share of high-tech investments. Finally, we find no evidence of a shortage of supply of venture capital funds, and no evidence of an effect of increased public R&D spending on the share of high-tech or early stage venture capital investments.
Keywords: G10; G24; H20; O30; 330; Barriers to Entrepreneurship; Capital Gains Tax; Public Policy; Public R&D Expenditure; Stock Markets; Venture Capital; Risikokapital; Wertzuwachssteuer; Öffentliche Forschung; Forschungskosten; EU-Staaten